The Influence of Knowledge Application on the Employability of Indonesian University Students with Internship Experience - Fahmi Jahidah Islamy; Abi Sopyan Febrianto (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
Bachelor's degree unemployment in Indonesia has increased steadily since 2022 despite the growing number of graduates entering the labor market. Knowledge management literature suggests that acquiring knowledge does not necessarily translate into the ability to apply it, whereas employers value knowledge application in workplace settings. This study tests that idea by looking at whether knowledge application predicts employability among 210 university students in Bandung, Indonesia, all of whom had completed an internship or a teaching practicum (PPL/P3K). Employability was measured across five dimensions: subject mastery, generic skills, career identity, personal flexibility, and career self-efficacy. Data were collected through a Likert-scale questionnaire, using purposive sampling, and analyzed with simple linear regression in SPSS. Both knowledge application and employability came out high overall, though career identity lagged behind the other four dimensions. The regression confirmed a positive, significant relationship (b = 0.527, t = 11.198, p < .001), with knowledge application explaining 37.6% of the variance in employability (R² = 0.376); the rest is presumably down to factors this study did not measure. These findings extend knowledge management theory by showing that the application dimension, not knowledge acquisition alone, is what carries over into labor-market readiness, a distinction current employability models rarely make explicit. For universities and internship providers, the practical implication is direct: structuring internships and teaching placements around real opportunities to apply coursework, rather than treating them as a formality, is likely to do more for graduate employability than adding further content to the curriculum.